Semiotic-Sufistic Interpretation of Imam Al-Ghazali: Case Study of "Verses of Light" in the Holy Qur'an - Habib, Habib; Habib, Moh (Indonesian Journal of Islamic Literature and Muslim Society, 2022)
Symbols play an important role in conveying the sufis’ spiritual experience. Describing their mystical journeys has been proven to be challenging because  their journeys occur outside common people’s realm of thinking. Their symbolic framework are only known by those who possess pure hearts and the knowledge of kashf  (a state of religious epiphany where someone was given the power by the God to see what others cannot see). Therefore, this study is aimed to analyze the interpretation of a semiotic-sufistic discourse by Imam Al-Ghazali (1057-1111) on “The Verses of Light” (the Holy Qur’an, Surah An-Nur, Verse No. 35) in one of his works Mishkat al-Anwar. The analysis was directed to some terminologies within the verses such as Allāhu nụrus-samāwāti wal-arḍ, misykât, mishbâh, zujâjah, syajarah mubârakah, and  al-zayt using semiotic-structuralism approach in order to unravel the Holy Qur’an’s semiotic structure and Al-Ghazali’s interpretation which is filled with mysterious symbolic/esoteric messages. The findings in this study indicate that 1) Al-Ghazali expressed his knowledge of ‘irfan (a form of religious and spiritual reality where God’s secrets are unveiled) by utilizing symbols due to difficulties in explaining such spiritual experience in empirical terms to other people; 2) Symbols are the most effective method to decipher messages obtained through kashf. This was the reason why Al-Ghazali chose to use symbols to interpret the messages within the Holy Qur’an; 3) Al-Ghazali’s thoughts about makna batin (the deep messages) can only be interpreted by sufi scholars specializing in mystical intuition method through the holy prophetic spirit. By using this method, these scholars can understand the deep messages behind the realm of al-Malakut (the unseen) through suluk, a way of life where people stick to the teachings of Islam very deeply and with extraordinary commitment to please Allah, the Almighty God